Corrosion of irradiated Ni-Mo alloys in sodium fluoride - zirconium melt - Azhazha, V.M.; Andriiko, A.A.; Bakai, A.S.; Volkov, S.V.; Devyatkin, S.V.; Dovbnya, A.N.; Lavrinenko, S.D.; Omelchuk, A.A.; Shirokov, B.M.; Shmegera, R.S. (Вопросы атомной науки и техники, 2005)
The corrosion of nickel-molybdenum alloys and their constituents in a molten eutectic sodium fluoride-zirconium fluoride mixture has been studied by cyclic voltammetry, X-ray analysis, SEM and metallography. The dependence of the corrosion rate of nickel-molybdenum alloys in molten fluorides on the time of soaking in melt and irradiation with an electron beam on an electron accelerator has been investigated. It has been shown that increasing the time of contact of nickel-molybdenum alloys with fluoride melt decreases the corrosion current density, and irradiation increases it in the greater extent the higher the electron beam energy. Intercrystalline corrosion is typical of the alloys of this composition.